Detection and classification of speed limit traffic signs - Biswas, Rubel; Fleyeh, Hasan; Mostakim, Moin (© 2014 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the World Congress on Computer Applications and Information Systems, WCCAIS 2014; Hammamet; Tunisia; 17 January 2014 through 19 January 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/WCCAIS.2014.6916605